PENCEMARAN NAMA BAIK MELALUI MEDI ELEKTRONIK DALAM PRESPEKTIF PUTUSAN PENGADILAN NOMOR 450/Pid.Sus/2017/PN.Smr TENTANG PENCEMARAN NAMA BAIK - Padli Padli (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTDefamation is also known as insult, which is basically attacking the good name and honor of someone who is not in a sexual sense so that the person feels wronged. Honor and good name have different meanings, but they cannot be separated from one another, because attacking honor will result in tarnished honor and good name, as well as attacking a good name will result in a person's good name and honor can be tainted.This type of research is included in the writing of normative law through a statutory approach.The results of this determination explain that the legal arrangements for defamation through electronic media have been regulated in article 27 paragraph (3) of law number 11 of 2008 concerning electronic information and transactions which reads: